Management of temporo-mandibular joint ankylosis in growing children - Shashikiran N; Reddy SV; Patil R; Yavagal G (Wolters Kluwer Medknow Publications, 2005)
Although temporo-mandibular joint (TMJ) ankylosis is one of the most common pathologies afflicting the facial skeleton, it is also the most overlooked and under-managed problem in children. The TMJ forms the very cornerstone of cranio-facial integrity and hence its ankylosis in growing children adversely affects the growth and development of the jaws and occlusion. Impairment of speech, difficulty in mastication, poor oral hygiene, rampant caries and acute compromise of the airway pose a severe psychologic burden on the tender minds of children. The aim of this article is to present an overview of efficient management strategies, based on a case report, so as to increase its awareness among all dental surgeons involved in the treatment of children.